Relationship between short duration and daily rainfall data in Kuala Lumpur - Salleh, Md. Noor; Al-Mamun, Abdullah; Mohamed Desa, Mohamed Nor; Mohamad Noor, Hanapi (2013)
Short duration rainfall is important for proper stormwater management in the existing and future urban areas and also for water resources study in small catchments. Unfortunately, many of the stations available in Malaysia are manual in nature and are able to provide daily rainfall data only. Despite the presence of numerous numbers of stations in Malaysia, the unavailability of rainfall data for the durations shorter than 24 hours is a hindrance in hydrologic and hydraulic analysis for small scale water resources projects. Therefore, an attempt was taken to study the correlation between daily rainfall and short duration rainfall less than 24 hours. The objective was to develop relations between daily rainfall and rainfall for any duration less than 24 hours. The study was conducted for selected seven (7) automatic rainfall stations in Kuala Lumpur, which were selected based on the length and quality of data available. Rainfall data of eleven different durations (15, 30, 45-min, 1, 2, 3, 6, 9, 12, 18 and 24-hr) were analysed to study the relationship with the daily rainfall data of each station. The median annual maximum 1-day rainfall value of the seven stations is 105 mm; whereas, the 90 and 10 percentile values are 125 and 73 mm, respectively. Analyses of the mean annual rainfall values of the selected durations revealed good pattern which can be used to estimate short duration rainfall based on the mean annual daily rainfall data. It was observed that the mean annual maximum rainfall data of 0.5, 1, 3, 6 and 12-hour durations are 45, 61, 76, 83 and 88% of the mean annual daily maximum rainfall in Kuala Lumpur area.